2016
DOI: 10.24914/jeb.v19i1.479
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Memengaruhi Perilaku Menabung Di Kalangan Mahasiswa

Abstract: High growth rate of savings will increase the rate of investment in Indonesia and ABSTRAKTingkat pertumbuhan tabungan yang tinggi akan meningkatkan laju investasi di Indonesia dan mendorong pertumbuhan ekonomi suatu bangsa. Survei yang dilakukan oleh Otoritas Jasa Keuangan (OJK), menunjukkan orang masih memiliki pemahaman yang rendah mengenai penggunaan produk keuangan termasuk tabungan. Hal ini juga ditunjukkan oleh posisi tabungan yang mengalami pertumbuhan menurun dari 2009-2013, terutama di Provinsi Jawa T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
27

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 14 publications
2
19
0
27
Order By: Relevance
“…Teori Harrod-Domar (dalam Wahana, 2014), menyatakan tingginya tingkat pertumbuhan ekonomi dipengaruhi oleh investasi dan tabungan yang tinggi pula. Teori yang sama oleh Rostow (dalam Sirine & Utami, 2016), menjelaskan suatu negara yang memiliki tingkat perekonomian yang kuat ialah dengan adanya tingginya tabungan masyarakat yang juga akan diperkuat dengan adanya investasi. Dalam siaran pers Widjanarko (2019) Direktur Eksekutif Bank Indonesia juga menyatakan bahwa akan terus berupaya mendorong perekonomian Indonesia dengan meningkatkan investasi untuk memitigasi perlambatan perekonomian dunia.…”
Section: Pendahuluanunclassified
“…Teori Harrod-Domar (dalam Wahana, 2014), menyatakan tingginya tingkat pertumbuhan ekonomi dipengaruhi oleh investasi dan tabungan yang tinggi pula. Teori yang sama oleh Rostow (dalam Sirine & Utami, 2016), menjelaskan suatu negara yang memiliki tingkat perekonomian yang kuat ialah dengan adanya tingginya tabungan masyarakat yang juga akan diperkuat dengan adanya investasi. Dalam siaran pers Widjanarko (2019) Direktur Eksekutif Bank Indonesia juga menyatakan bahwa akan terus berupaya mendorong perekonomian Indonesia dengan meningkatkan investasi untuk memitigasi perlambatan perekonomian dunia.…”
Section: Pendahuluanunclassified
“…Following the theory of planned behavior (TPB), it is stated that subjective norm is one of the factors influencing saving behavior in which parties related to subjective norms come from their immediate environments such as parents, family, or teachers. Thus the role is potentially empowered to encourage saving behavior (Jamal et al, 2015); (Widyastuti et al, 2016); (Garcia et al, 2011); (Sirine & Utami, 2016). Based on these studies, it is concluded that the family environment has a strong influence on saving behavior so that to foster children's behavior it is necessary to involve those who have closest relationship to the children.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable (Y) in this study was the behaviors of saving money. Such behavior used in this study was measured through the statements of Sirine [13]. The independent variable in this study was gender (X1), the measurement of which was based on the research conducted by Kostakis [14]; age (X2) which was measure through scoring based on Popovici's [14] study; education level (X3) which was measured scoring based on the study done by Margaretha [16]; income (X4) which was measured through scoring based on the study carried out by Ida [17]; marital status (X5), the measurement of which was based on the study done by Kostakis [14]; amount of burden (X6), which was measured though burden ratio.…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…Parents (X7) and peers (X8) were measured by Sirine's statements [13] that have been adapted. Financial self-efficacy (X9) in this study was measured by Farrel's statement [19].…”
Section: Social Cognitive Theorymentioning
confidence: 99%